Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s41021-015-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic integration of lambda EG10 transgene in gpt delta transgenic rodents

Abstract: BackgroundTransgenic gpt delta mouse and rat models were developed to perform gpt and Spi− assays for in vivo mutagenicity tests. The animals were established by integration of lambda EG10 phage DNA as a transgene into the genome. The inserted position of the transgene on chromosome was determined by fluorescent in situ hybridization and Southern blot analyses; however, the exact position and sequence of the inserted junction were not known. To identify the site and pattern of genomic integration of the transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…A λ‐EG10‐based transgenic C57BL/6 mouse model was specifically designed to facilitate in vivo detection of genomic point mutations and large deletions . It has been estimated by whole genome sequencing that C57BL/6 gpt delta mice carry tandem arrays of approximately 40 copies of the bacterial guanine phosphoribosyltransferase gene ( gpt ) at a single site on chromosome 17 . In this experimental in vivo system, point mutations can be detected and quantified by 6‐thioguanine (6‐TG) selection, whereas deletions up to 10 kb in length are characterized by selection based on sensitivity to P2 interference (Spi − ) .…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…A λ‐EG10‐based transgenic C57BL/6 mouse model was specifically designed to facilitate in vivo detection of genomic point mutations and large deletions . It has been estimated by whole genome sequencing that C57BL/6 gpt delta mice carry tandem arrays of approximately 40 copies of the bacterial guanine phosphoribosyltransferase gene ( gpt ) at a single site on chromosome 17 . In this experimental in vivo system, point mutations can be detected and quantified by 6‐thioguanine (6‐TG) selection, whereas deletions up to 10 kb in length are characterized by selection based on sensitivity to P2 interference (Spi − ) .…”
Section: Introductionsupporting
confidence: 84%
“…15 It has been estimated by whole genome sequencing that C57BL/6 gpt delta mice carry tandem arrays of approximately 40 copies of the bacterial guanine phosphoribosyltransferase gene ( gpt) at a single site on chromosome 17. 16 In this experimental in vivo system, point mutations can be detected and quantified by 6-thioguanine (6-TG) selection, whereas deletions up to 10 kb in length are characterized by selection based on sensitivity to P2 interference (Spi − ). 15 We previously demonstrated that H. pylori SS1 infection in C57BL/6 gpt delta mice promoted point mutation frequencies in gastric mucosa in females but not in males compared to uninfected controls, whereas no difference in large deletions was noted.…”
Section: Introductionmentioning
confidence: 99%
“…If ENU-induced germline gpt mutations are transmitted to offspring, then a very high gpt mutant frequency could be observed in the F1 mice. It has been reported that there are approximately 40 copies of each transgene per haploid in gpt delta mice [ 38 ]. If one copy contains the inherited gpt mutation, then the expected mutant frequency in the F1 mice would be 1/80 = 12.5 × 10 −3 , which is 1000 times higher than the control level.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation frequency was calculated by dividing the number of unique mutations by the total number of colonies (for all calculations, the respective dilution factors were taken into account). Furthermore, to focus on the kinetics of mouse cell survival after exposure to ENU, the mutant frequency per cell was calculated based on 40 copies of the transgene per cell [Masumura et al, ]. Each cell was assumed to contain no more than one mutant transgene in its 40 transgene cassette; thus we converted mutant transgene frequency to mutant cell frequency as follows:…”
Section: Methodsmentioning
confidence: 99%